(untitled) (World Bulletin of Public Health, 2023)
Today, the number of diseases that lead to dentoal veolar anomalies and indirect factors affecting them, the decrease of attention given to children by parents, shows the increase of this disease. Early diagnosis of clinical signs of disease in orthodontic patients, restoration of physiological functions of chewing efficiency in children is one of the urgent problems of children’s orthodontic dentistry today.